Digital Learning Ecosystems and Learning Outcomes in Islamic Education: The Role of Mobile Learning, Digital Resources, and Instructional Models - Fathul Janah; Mohammad Salehudin; Siti Rosilawati Ramlan (Dirasah International Journal of Islamic Studies, 2026)
This research aims to investigate whether mobile learning, digital learning resources, and learning models have a significant influence on the learning outcomes of Islamic Religious Education. The study employs a quantitative approach using a survey research design, drawing a sample of 145 respondents through random sampling. Data collection is conducted using instruments that have been tested for validity and reliability. Data analysis is performed using Structural Equation Modelling (SEM) with Partial Least Squares (PLS) version 4.0. The study's findings reveal that mobile learning (ML) does not have a significant effect on Islamic Religious Education Learning Outcomes (IRELO) and is therefore rejected. Conversely, the variables of Digital Learning Resources (DLR) and Learning Model (LM) show a significant influence on IRELO and are accepted. Consequently, this research identifies a substantial impact among the variables, aligning with the ongoing digital transformation in education. It is imperative that both educators and students effectively utilise digital learning resources and mobile learning in their educational practices to ensure the attainment of educational objectives. The best learning model is not a single, rigid formula, but rather the one that best suits the instructional objectives, material characteristics, and students' specific needs, and whose development is fully supported by the completeness of digital learning resources. This research is crucial for the ultimate goal of enhancing the quality of education and cultivating a golden generation for Indonesia by the year 2045.